2009
DOI: 10.1242/jcs.043034
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocytoplasmic shuttling of soluble tubulin in mammalian cells

Abstract: We have investigated the subcellular distribution and dynamics of soluble tubulin in unperturbed and transfected HeLa cells. Under normal culture conditions, endogenous α/β tubulin is confined to the cytoplasm. However, when the soluble pool of subunits is elevated by combined cold-nocodazole treatment and when constitutive nuclear export is inhibited by leptomycin B, tubulin accumulates in the cell nucleus. Transfection assays and FRAP experiments reveal that GFP-tagged β-tubulin shuttles between the cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…In our fractions that were verified to be nuclear fractions, ␤-tubulin was present. ␤-Tubulin was used as a loading control to normalize FoxO1 expression, because its presence in both the cytoplasm and nucleus has been previously verified (1,66,71).…”
Section: Cell Fractionationmentioning
confidence: 99%
“…In our fractions that were verified to be nuclear fractions, ␤-tubulin was present. ␤-Tubulin was used as a loading control to normalize FoxO1 expression, because its presence in both the cytoplasm and nucleus has been previously verified (1,66,71).…”
Section: Cell Fractionationmentioning
confidence: 99%
“…From this they inferred that the form adopted by keratin inside the nucleus is fundamentally distinct from that occurring in the cytoplasm (10-nm IFs). Other cytoskeletal proteins, including actin (Schoenenberger et al, 2005) and tubulin (Akoumianaki et al, 2009), have been shown to adopt a distinct conformation while inside the nucleus, correlating with their association with a distinct set of protein partners. Going forward, identifying these regulatory factors (i.e., post-translational modifications and/or unique interacting protein partners) represents a fundamentally important though technically challenging aspect of understanding the significance of nuclear-localized keratins.…”
mentioning
confidence: 99%
“…When soluble tubulin subunits accumulate in the nucleus, the cell cycle progression is inhibited. Nuclear accumulation of β-tubulin does not occur under normal circumstances suggesting that this is a pathophysiological process and may represent a defense mechanism against stress or malignant transformation (Akoumianaki, et al, 2009). In the case of primary hepatocytes exposed to 30 nM OA or DTX-2, nuclear accumulation of β-tubulin could be a consequence of the chemical stress induced by these compounds.…”
Section: Discussionmentioning
confidence: 99%